Komunikasi Komunitas Regas Dalam Mempertahankan Eksistensi Sastra Jawa di Yogyakarta - Buana, Mufti Putri Dewi; Amali, Muhammad Thoyib (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Currently, Javanese literature has experienced a crisis of decline and is even threatened with extinction in Indonesia. In fact, Javanese literature itself is a representation of ideas, norms, and views of Javanese society. The aim of the research is to determine the communication strategy of the Geblek Bersastra Youth Community in maintaining the existence of Javanese literature among Yogyakarta teenagers. The research was conducted using a qualitative approach with the case study method. Data collection took the form of interviews, observations and documentation which were analyzed using triangulation techniques to examine data from various sources in various ways and at various times. The research results showed that the Geblek Bersastra Youth Community has used good communication strategies, with the communication target being teenagers who live in Yogyakarta and often use Instagram to share informative and up-to-date community activities. Apart from that, the Regas Community also invites participants and members without coercion, and uses credible sources and facilitators to make teenagers interested in taking part in Javanese Literature. activities. This is what makes the Regas Community much sought after by teenagers in Yogyakarta with the indicators mentioned.